Regulatory Framework on Compensation for the Restoration of Victims of Sexual Violence - Purwadi, Hari; Lukitasari, Diana; Mayastuti, Anti; Abd Aziz, Hartinie; Cahyaningtyas, Irma (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2024)
Compensation for crime victims based on Law Number 12 of 2022 concerning Anti Sexual Violence has the potential for distortion due to the regulatory framework and the enforcement process. The article aims to examine the regulatory framework that ensures compensation as an instrument of victim restorations, whether it becomes a supplement or a substitution for restitution. Research methods using the upstream and downstream process models that emphesize regulatory design and process feasibility for payments, in which compensation has a role in victim recovery. The study result explain that compensation is formally a substitution for restitution. Compensation is not the primary goal, even though it is a state’s obligation. Law Number 12 of 2022 concerning Anti Sexual Violence thus emphasizes the use of direct restitution aimed at the recovery of victims and the rehabilitation of offenders. Compensation loses its meaning as a responsibility of the state that stands alone. Data from various decisions clarify that in cases where the offenders does not pay restitution, their property is confiscated and auctioned by the prosecutor to pay restitution. If it is insufficient, courts decide that imprisonment is a substitute and do not determine that the state has to pay compensation.